Driver of returns to schooling: Education-related policies or family background? - Jan-Jan Soon; Hock-Eam Lim (Global Labor Organization (GLO), 2024)
Does schooling pay off? - a seemingly straightforward question, but it is in fact a puzzle among economists. Answers would differ based on how the returns to schooling are estimated. Among the top concerns is whether such estimations have any causal connotation between the amount of schooling and its returns or earnings. The endogeneity issue arises due to ability bias, where ability is typically related with years of schooling. The impact of schooling would be confounded by ability, hence the difficulty in isolating schooling's causal impact on earnings. To address the concern, we conduct a meta-analysis of 74 empirical studies from which we retrieve returns to schooling coefficients estimated using both the causal instrumental variable and non-causal naïve estimation approaches. Key findings from our meta-analysis suggest an overall impact of 0.898, meaning an additional year of schooling is associated with a 8.98% increase in earnings, on average. We also find that over the years, returns to schooling exhibit an upward trend in general. Probing deeper, our analyses provide statistical evidence that education-related policy factors are driving the results more than family background factors.
Keywords: C50; I26; I28; 330; Returns to schooling; meta-analysis; family background; education-related policy